Causes and treatments of lag screw’s cut out after intramedullary nailing osteosinthesis for trochanteric fractures - Gazzotti, Gabriele; Matino, Giovanni; Tsatsis, Christos; Sacchetti, GianLuigi; Baudi, Paolo; Catani, Fabio (Acta Biomedica Atenei Parmensis, 2014)
Background. Superior cut-out of a lag screw remains a serious complication in the treatment of trochanteric or subtrochanteric fractures and it is related to many factors: the type of fracture, osteoporosis and the stability of fracture reduction. Little is known about the outcome after revision surgery for complications of the gamma nail. We assessed the outcome in patients who had revision surgery because of lag screw’s cut out after gamma nailing for a trochanteric fracture. Material and Method. We present a study of 20 consecutive patients who underwent treatment after 20 cut-out of the lag screw ﬁxation of a trochanteric fracture with Gamma Locking Nail from September 2004 to November 2010. In 16 patients hip prothesis was performed, in 1 the removal of the implant and in 3 the reosteosynthesis. We reviewed 13 patients: 10 total hip arthroplasty, 2 endoprothesis and 1 reosteosynthesis of nail and lag screw (mean follow up: 26 months, mean age: 73 years old), 7 patients died. Patients were reviewed retrospectively by an independent observer. Clinical evaluation was performed, Oxford score and Harris Hip score were measured. X-Ray examination was performed after a minimum of 12 months of follow up. Results. Mean Harris Hip Score mean was 67 and mean Oxford score was 32 in hip prothesis group (12 patients). We had several complications, Implant-related complications were: 2 ipometria > 2cm, 2 recurrent hip arthroplasty dislocations (1 reoperated), 4 persistent thigh pain. In only 4 patients none complications were observed. Another patient, who had been subjected to reosteosinthesis, obtained better results (HHS:95, Oxford score:45) but with a 2 cm ipometria and occasional pain in the thigh. Conclusion. Cut out after gamma nail is consequent to biological or mechanical causes. Treatment of this complication is hip prosthesis (parzial or total hip arthroplasty), reosteosynthesis of the lag screw and/or the nail and the removal of the implant. Conversion to total/parzial hip arthroplasty may be a demanding operation with a higher complication rate respect to the standard, while reosteosynthesis is possible in selected patients and early cutting out.